FAILURE TO PROVIDE INFORMATION OF CRIME OR PERPETRATOR AS A PROBLEM OF CRIMINAL LAW - Korosec, Damjan (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
At least in Europe there are several legal systems incriminating the omission of providing formal information of crime or perpetrator (to provide a report of crime or perpetrator) to certain state authorities (police, public or state prosecutors). A typical such incriminative norm is a combination of a so-called long-term crime and objective condition of punishability. This combination rises rather complex dogmatical problems and endangers as a final consequence the legal safety of citizens as potential perpetrators of such omissive mass crimes. The author shows the example of Slovenian substantive criminal law and calls for more effective comparative criminal law cooperation between legal systems especially in deciding about abolishing the more and more controvert institute of objective condition of punishability altogether.